2009
DOI: 10.1080/13645700902921575
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for the resection of aortic valves: In-vitro results for turning moments and forces using Nitinol cutting edges

Abstract: The use of minimally invasive techniques for aortic valve replacement (AVR) may be limited for severely calcified and degenerated stenotic aortic valves. A quick resection leaving a defined geometry would be advantageous. Therefore, a new minimally invasive resection tool was developed, using rotating foldable cutting edges. This report describes the first experimental in-vitro results of measuring turning moment and forces during cutting of test specimens. Nitinol cutting edges were mounted on a simplified ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Whether these leaflets have any mechanical impact on the TAV intervention is currently unclear. It has been suggested that these calcified leaflets be removed prior to the TAV intervention by a separate minimally invasive means 37 . Our simulation results showed that high stress concentrations (Table 2) were seen around the calcified regions in the leaflets as well as at the attachment lines of leaflets and the aortic sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these leaflets have any mechanical impact on the TAV intervention is currently unclear. It has been suggested that these calcified leaflets be removed prior to the TAV intervention by a separate minimally invasive means 37 . Our simulation results showed that high stress concentrations (Table 2) were seen around the calcified regions in the leaflets as well as at the attachment lines of leaflets and the aortic sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 These surgical alternative options may be potentially incorporated into routine AVR programs in the foreseeable future as a capable treatment option for mid-or low-risk groups. By the use of sutureless heart valves (SHV) and other innovative tools, 7 a new field in heart surgery with less invasiveness and implantation time may improve outcomes for patients and potential cost reduction.…”
mentioning
confidence: 99%